?SYNTHESIS OF SOME NEW NITROGENOUS DERIVATIVES OF GLYCYRRHETIC ACID WITH POTENTIAL BIOLOGICAL ACTIVITY (Biological Sciences - PJSIR, 1995)
The synthesis of some nitrogenous derivatives from glycyrrhetic acid hydrazides (III) by incorporating its C-30 toform 1', 3', 4'-oxadiazole (V), 4'-acetyl-5-aryl-1'-oxadiazoline (VII), 1',3',4'-triazole (X), carboxymethyl thiotriazole(XII) and 1',3',4'-thiodiazoline-5'-thion (XIII) rings are reported. The reactions of the hydrazide III with aromatic aldehydes,thiocyanates, isocyanates and its 3-acetyl derivative (XVI) with aniline and ethyl glycinate were studied. The antimicrobialactivity of some derivatives was tested against some microorganisms.